Pertumbuhan Awal Bibit Malapari Hasil Stek Batang setelah Pemberian Pupuk Kompos dan NPK - Adinugraha, Hamdan Adma; Luti, Mekianus (Universitas Muhammadiyah Surakarta, 2022)
Provision of seedlings for planting material of Pongamia pinnata can be done vegetatively using stem cuttings technique. This study aims to determine the effect of compost and NPK fertilizer dosage on the initial growth of Pongamia sp seedlings from stem cuttings. The study was arranged in a completely randomized design with a factorial pattern consisting of 2 factors. The first factor is a medium consisting of 2 levels, namely soil without compost (M1) and a mixture of soil and compost with a ratio of 3:1 (M2). The second factor was NPK fertilization which consisted of 4 levels, namely without fertilization/control (P0), fertilized with NPK 1 gram/polybag (P1), 2 grams/polybag (P2) and 4 grams/polybag (P4). NPK fertilization is done 2 times with an interval of one month. The results showed that at the age of 3 months of seedlings, compost and NPK had a positive effect on the growth of seedling height and diameter, although not significantly different. The average height of 3 month oldseedlings ranged from 25.50-33.20 cm with a total height increase of 9.50 -16.60. The average seedling diameter was 3.90-4.20 mm with an increase in the total diameter of about 1.40-1.60 mm and the average seedling sturdiness value was 6.30-7.90.